A study on selected Palanca Award winning short stories in Hiligaynon from 1997-2003 feminist reading - Mallorca, Airene L.
The Don Carlos Palanca Memorial Awards for Literature aims to help develop Philippine Literature by providing incentives for writers to craft their most outstanding literary work and to be a treasury of the Philippine?s literary gems from our gifted writers and to assist in its eventual dissemination to the people, particularly the students. The study of A Study on Selected Palanca Award-Winning Short Stories in Hiligaynon from 1997-2003 through the Feminist Reading aims to know how Ilonggas are portrayed in the short stories and what the differences are in the conceptualization of men and women as found in the female-authored texts and the male-authored texts. In the male-authored texts, men are providers and women are victims. In female-authored texts, men are passive and women are individualistic. Ilonggas are perceived as independent, as an individual, a fair and understanding partner in a relationship, and an intellectual. Ilonggas, based on the short stories, may be helpless and inferior at times but they resist the dominance and the stereotyping by the patriarchal society. In fact, with every dominance, there is rebirth of character. Ilonggas are celebrated in the Hiligaynon literature.